2019
DOI: 10.1002/app.47624
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and optical, electrochemical, and photovoltaic properties of polymers with 6‐(2‐thienyl)‐4H‐thieno[2,3‐b]indole with a variety of electron‐deficient units

Abstract: Conjugated polymers were synthesized and used for polymer solar cells with new electron-rich units, 6-(2-thienyl)-4H-thieno [2,3-b]indole (2-TTI). 2-TTI was coupled with electron-pulling units, including benzothiadiazole and benzimidazole derivatives, to provide push-pull types of conjugated polymers (poly(8-(heptadecan-9-yl)-6-(thiophen-, and poly(8-(heptadecan-9-yl)-6-(thiophen-2-yl)-8H-thieno[2,3-b]indole)-alt-(2,2-dimethyl-5,6-bis(octyloxy)-4,7-di(thiophen-2-yl)-2H-benzimidazole) (PTTIDOMBI)). The synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The indole core fused with carbo or hetero rings constitutes a recurring framework of derivatives endowed with significant biological and medicinal properties and therefore subject of considerable attention . In this context, interesting examples are represented by the indole-annulated heterocycles containing sulfur atoms that display relevant properties such as antifungal, anticancer, anti-inflamatory, antihyperplasia, analgesic, antibacterial ones, antipsychotic activities or that were employed in the construction of small efficient push–pull chromophores . They are also found in several cruciferous phytoalexins, e.g., cyclobrassinin, spiro-brassinin, or brassicanal B, employed as plant defense chemicals .…”
Section: Introductionmentioning
confidence: 99%
“…The indole core fused with carbo or hetero rings constitutes a recurring framework of derivatives endowed with significant biological and medicinal properties and therefore subject of considerable attention . In this context, interesting examples are represented by the indole-annulated heterocycles containing sulfur atoms that display relevant properties such as antifungal, anticancer, anti-inflamatory, antihyperplasia, analgesic, antibacterial ones, antipsychotic activities or that were employed in the construction of small efficient push–pull chromophores . They are also found in several cruciferous phytoalexins, e.g., cyclobrassinin, spiro-brassinin, or brassicanal B, employed as plant defense chemicals .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the processability of PIN is an important factor to be addressed for better applicability in various fields. In the literature, PIN has been modified in a variety of ways, including the addition of substitute groups in the main chain, the synthesis of soluble precursors, the preparation of composites through chemical oxidation methods and the blending of PIN with one or more flexible and stable polymers 6–8 . Recent reports have shown that the fabrication of PIN composites by chemical oxidative polymerization methods has drawn much attention, due to its easy and effective nature 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, PIN has been modified in a variety of ways, including the addition of substitute groups in the main chain, the synthesis of soluble precursors, the preparation of composites through chemical oxidation methods and the blending of PIN with one or more flexible and stable polymers. [6][7][8] Recent reports have shown that the fabrication of PIN composites by chemical oxidative polymerization methods has drawn much attention, due to its easy and effective nature. 9 This chemical oxidative method can also be used to increase the length of the polymer chain to the desired length.…”
mentioning
confidence: 99%
“…1). 5 A natural product worthy of particular attention is the thienodolin, an amido substituted thieno[2,3- b ]indole isolated from Streptomyces albogriseolus whose biological properties include plant–growth regulatory capacity and the nitric oxide synthase inhibition (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%